Biased Signaling and Allosteric Modulation at the FSHR - Landomiel, Flavie; De Pascali, Francesco; Raynaud, Pauline; Jean-Alphonse, Frédéric; Yvinec, Romain; Pellissier, Lucie P.; Bozon, Véronique; Bruneau, Gilles; Crépieux, Pascale; Poupon, Anne; Reiter, Eric (Frontiers in Endocrinology, 2019)
Knowledge on G protein-coupled receptors (GPCRs) structure and mechanism of activation has profoundly evolved over the past years. The way drugs targeting this family of receptors are discovered and used has also changed. Ligands appear to bind a growing number of GPCRs in a competitive or allosteric manner to elicit balanced signalling or biased signalling (i.e.: differential efficacy in activating or inhibiting selective signalling pathway(s) compared to the reference ligand). These novel concepts and developments transform our understanding of the follicle-stimulating hormone (FSH) receptor (FSHR) biology and the way it could be pharmacologically modulated in the future. The FSHR is expressed in somatic cells of the gonads and plays a major role in reproduction. When compared to classical GPCRs, the FSHR exhibits intrinsic peculiarities, such as a very large NH2-terminal extracellular domain that binds a naturally heterogeneous, large heterodimeric glycoprotein, namely FSH. Once activated, the FSHR couples to Gs and, in some instances, to other G subunits. G protein-coupled receptor kinases and -arrestins are also recruited to this receptor and account for its desensitization, trafficking and intracellular signalling. Different classes of pharmacological tools capable of biasing FSHR signalling have been reported and open promising prospects both in basic research and for therapeutic applications. Here we provide an updated review of the most salient peculiarities of FSHR signalling and its selective modulation.